Effect of an oxygen-free atmosphere during heating on anthocyanin, organic acid, and color of strawberry puree. (December 2022) - Kim, Ah-Na; Lee, Kyo-Yeon; Han, Chae-Yeon; Kim, Hyun-Jin; Choi, Sung-Gil
Abstract: Strawberries were ground and heated under oxygen-free condition using a specially designed device, and compared with the berries processed at atmospheric condition. The complete inactivation of oxidative enzymes and microorganisms were found in both samples. The heating without oxygen led to higher concentrations of anthocyanins and organic acids than with oxygen, resulting in higher redness and antioxidant activity. Particularly, the greatest effect of anaerobic condition was observed in delphinidin-3-glycoside and ascorbic acid which are the most sensitive to oxidation in presence of oxygen. However, some nutrients which are low dependence on oxygen were degraded regardless of insufficient oxygen. It was considered that anaerobic condition may inhibit the deterioration related to only oxidation, not non-oxidative reaction during heating. Microscopic results implicated that dissolved oxygen in tissues may cause continuous oxidative deterioration. In summary, oxygen-free condition can confer better oxidative stability of antioxidants and color during heating of berry products. Highlights: Strawberry was sequentially ground, packaged, and heated without oxygen. Oxygen-free condition led to prevent oxidation and discoloration during heating. Heating without oxygen is most effective in retaining delphinidin and ascorbic acid. Delphinidin and ascorbic acid were highest oxygen-dependent antioxidants. Dissolved oxygen may be attributed to continuous oxidation during heating.